Konsumsi pangan dan skor pola pangan harapan (PPH) dengan prevalensi stunting di Provinsi Aceh (Data Susenas dan PSG tahun 2016) - Suryana Suryana; Roudza Roudza; Alfridsyah Alfridsyah (AcTion: Aceh Nutrition Journal, 2018)
Stunting in toddlers is one of the big problems that can threaten the development of the Quality of Human Resources, that can have an impact on national development. Quality human resources can be obtained by consuming adequate food, both in quantity, quality and balance. Associated with the problem of stunting food consumption in Aceh Province based on the Score Desirable Dietary Pattern as DDP is still less than DDP ideal is 70.0. This study aims to determine the association of food consumption and the Hope Food Pattern score with the prevalence of stunting in Aceh Province. This research is a descriptive analytic with the Cross-Sectional. Study design. The study used secondary data, National Census data analysis and Nutritional Status Monitoring 2016. The analysis used is a regression. The results showed that the average energy and protein consumption in households in Aceh Province was 2.276 kcal of energy and 65,21 grams of protein. The average energy and protein consumption are in the normal category of 105,8% (energy) and 114,0% (protein). The diversity of food consumption has not been varied enough based on the average score in Aceh Province is 77,8. Stunting is a public health problem with a mild problem category known from the average value of stunting prevalence of 26,3%. There was no relationship from AKE (p= 0,430), PPA (p= 0,274) and PPH score (p= 0,259) with stunting prevalence based on District / City in Aceh Province in 2016. The conclusion is There was no significant relationship between stunting and Energy Adequacy Rate (AKE), Protein Adequacy Rate (PPA), and Score DDP.Sumber daya manusia yang dapat berakibat pada pembangunan nasional. Terkait dengan masalah stunting konsumsi pangan di Provinsi Aceh berdasarkan Skor Pola Pangan Harapan (PPH) masih kurang dari ideal yaitu 70,0. Penelitian ini bertujuan untuk mengetahui keterkaitan konsumsi pangan dan skor Pola Pangan Harapan (PPH) dengan prevalensi stunting di Provinsi Aceh . Penelitian ini bersifat deskriptif analitik dengan desain Cross Secsional Study. Penelitian menggunakan data sekunder yaitu data konsumsi (Susenas) dan data stunting balita survei (PSG). Pengumpulan data dengan cara wawancara menggunakan kuesioner food list (data konsumsi pangan), sementara data status gizi dengan cara penimbangan berat badan pengukuran tinggi badan. Analisis  yang digunakan adalah  korelasi regresi. Hasil penelitian menunjukkan rata-rata konsumsi energi dan protein pada rumahtangga di Provinsi Aceh adalah sebesar 2.276 kkal energi dan 65.21 gram protein.  Rata-rata  konsumsi energi dan protein pada rumah tangga di Provinsi Aceh berada pada kategori normal 105,8% AKE dan 114,0% AKP. Keragaman pangan konsumsi pangan belum cukup beragam diketahui berdasarkan nilai rata-rata  skor PPH sebesar 77,8,  skor maksimum 92,5 dan skor minimum 64,2. Masalah stunting merupakah masalah kesehatan masyarakat dengan kategori masalah ringan diketahui dari nilai rata-rata prevalensi stunting sebesar 26,3%. Tidak terdapat hubungan AKE (P=0,430), AKP (p=0,274) dan skor PPH (p=0,259) dengan prevalensi stunting. Kesimpulan adalah tidak terdapat hubungan yang signifikan antara stunting dengan Angka kecukupan Energi (AKE), Angka Kecukupan Protein (AKP), dan Skor PPH.